BIOMASS AND ENERGY YIELD OF LEGUMINOUS TREES CULTIVATED IN AMAZONAS - Pires da Costa, Karen Cristina; Bezerra de Lima, Roberval Monteiro; Ferreira, Marciel José (Floresta, 2015)
Abstract Energy forests emerge as an alternative to fossil fuels for energy production. The good performance of these forests should consider the selection of fast-growing species, high biomass productivity and energy yield. The aim was to investigate growth and energy yield of Acacia auriculiformis and Acacia mangium in a short-rotation plantation in the Amazonas. The energy yield was determined on 12 trees per species, from the results of biomass, calorific value and basic density. When 9 years-old, A. mangium had the highest growth rates in height (1.9 m yr-1) and DBH (2.5 cm yr-1). The greatest biomass productivity was observed in A. mangium (33.4 Mg ha-1 yr-1), which was 84% higher than A. auriculiformis (18.1 Mg ha-1 yr-1). Basic density (0.54 g cm-3) and calorific value (4,400 kcal kg-1) showed no significant differences between species. The energy yield of A. mangium (1,317 Gcal ha-1) was twice as of A. auriculiformis (684 Gcal ha-1). A. mangium has better energy performance, compared to the A. auriculiformis, and therefore could the most recommended for the formation of energy forests in disturbed areas in the state of Amazonas. Resumo Biomassa e produtividade energética de leguminosas arbóreas cultivadas no Amazonas. As florestas energéticas representam alternativa à dependência do uso de combustíveis fósseis para a produção de energia. O bom desempenho dessas florestas deve considerar a seleção de espécies de rápido crescimento, alta produtividade em biomassa e rendimento energético. O objetivo foi investigar o crescimento e a produtividade energética de Acacia auriculiformis e Acacia mangium em plantios florestais de curta rotação no Amazonas. A produtividade energética foi determinada em 12 árvores de cada espécie, a partir dos resultados de biomassa, poder calorífico e densidade básica. Aos 9 anos, A. mangium teve as maiores taxas de crescimento em altura (1,9 m ano-1) e DAP (2,5 cm ano-1). A maior produtividade de biomassa foi observada em A. mangium (33,4 Mg ha-1 ano-1), que foi 84% superior a de A. auriculiformis (18,1 Mg ha-1 ano-1). A densidade básica (0,54 g cm-3) e o poder calorífico (4.400 kcal kg-1) não apresentaram diferenças significativas entre as espécies. A produtividade energética de A. mangium (1.317 Gcal ha-1) foi duas vezes maior que a de A. auriculiformis (684 Gcal ha-1). Acacia mangium tem melhor desempenho energético quando comparada à A. auriculiformis, sendo portanto mais recomendada para a formação de florestas energéticas em áreas alteradas no estado do Amazonas. Palavras-chave: Acacia mangium; Acacia auriculiformis; plantios de curta rotação.